2013
DOI: 10.3184/174751912x13549029453945
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of new Derivatives of Pyrimido[5,4-e][1,2,4]triazolo[3,4-b] [1,3,4]Thiadiazine and Their Enzyme Inhibitory Activity Assessment on Soybean 15-lipoxygenase

Abstract: The synthesis of new derivatives of pyrimido [5,4-e][1,2,4]triazolo[3,4-b][1,3,4]thiadiazine is described. These derivatives have a wide range of medicinal applications. Their inhibitory activity against the enzyme 15-lipoxygenase was also investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…After the completion of the reaction, the mixture was concentrated and the resultant precipitates were collected by filtration. Synthesis of substituted-6-phenyl- [1,2,4]tetrazolo- [5,1-b] [1,3,4] thiadiazines (4a-g); general procedure A mixture of 2 (1 mmol) and the substituted phenacyl bromide (1 mmol) in acetic acid (5 mL) was refluxed for about 4 h. The progress of the reaction was monitored by TLC using chloroform: methanol (20 : 1). After the completion of the reaction, the mixture was concentrated and the resultant precipitates were collected by filtration.…”
Section: Synthesis Of 6-methyl-7h-tetrazolo[51-b][134]thiadiazine mentioning
confidence: 99%
“…After the completion of the reaction, the mixture was concentrated and the resultant precipitates were collected by filtration. Synthesis of substituted-6-phenyl- [1,2,4]tetrazolo- [5,1-b] [1,3,4] thiadiazines (4a-g); general procedure A mixture of 2 (1 mmol) and the substituted phenacyl bromide (1 mmol) in acetic acid (5 mL) was refluxed for about 4 h. The progress of the reaction was monitored by TLC using chloroform: methanol (20 : 1). After the completion of the reaction, the mixture was concentrated and the resultant precipitates were collected by filtration.…”
Section: Synthesis Of 6-methyl-7h-tetrazolo[51-b][134]thiadiazine mentioning
confidence: 99%
“…12 In addition, triazolopyrimidopyridazine derivatives are obtained from heating of 5,6-dihydro-7-hydrazino-5-imino-3,4,6triphenylpyrimido [4,5-c]pyridazine with CS 2 , triethylorthoformate in acetic acid or condensation with aromatic aldehydes. 13,14 As part of our ongoing studies dealing with the synthesis of new biologically active heterocyclic compounds, [15][16][17] we now report the synthesis and structural elucidations of various pyrimido [4,5-c]pyridazines as precursors for the synthesis of the novel [1,2,4]triazolo[4′′,3′′:1′,6′]pyrimido[4′,5′: 3,4] pyridazino [1,6-d] [1,2,4]triazine system and its derivatives.…”
mentioning
confidence: 99%
“…15 It is well known that pyrimidine and fused pyrimidines are of great biological interest, especially as antiviral, antitumor and antimicrobial agents. 16 As a continuation of our work on the synthesis of biologically active heterocyclic compounds, [17][18][19] we became interested in the synthesis of pyrimido[5′,4′:5,6] [1,4] thiazino [2,3-b]quinoxalines. A literature survey revealed that there is only one reference dealing with the synthesis of this heterocyclic system, employing 4,5-diaminopyrimidine-6(1H)thione and 2,3-dichloroquinoxalines as the starting materials.…”
mentioning
confidence: 99%